Implementation of Undulating Training Periodization based on training objectives on Increasing Power Endurance - Umaran, Unun; Zaky, Mohammad; Imanudin, Iman (Indonesian Journal of Sport Management, 2024)
: In an effort to improve the performance of athletes in sports, there is no other way than by training, practicing seriously and earnestly guided by a well-planned and arranged training program. The phenomenon that often occurs is that there are still many trainers who do not understand how to determine the dose of the right training aspects and in accordance with the needs of athletes and the demands of sports with the situation and conditions of uncertain sports calendarization. Therefore, it is necessary to model or engineer training so that with the time available, a little training process can be useful and meaningful for improving the physical quality of athletes. The purpose of this study was to determine the impact of the application of undulating training periodization based on exercise goals on increasing power endurance. The research method is experimental, with the design used is one group pretest-posttest, and the sample is 15 people. The power endurance instrument used is the multistage hurdle jump test to measure the lower body, and the clapping push up test to measure the upper body. For data analysis using paried sample t test. The results showed that there was an increase in power endurance after being given a strength training program with undulating periodization based on exercise goals, both for the lower body and upper body. This is evidenced by the results of data processing which shows the significance value of lower body and upper body power endurance 0.00 <0.05. The conclusion is that the application of an exercise program with undulating periodization based on exercise objectives has a significant impact on increasing power endurance.